PENGEMBANGAN BAHAN AJAR MAHĀRATUL KALĀM BERBASIS KEARIFAN LOKAL PROVINSI GORONTALO - Laubaha, Siti Aliyya; Otaya, Lian G; Yasin, Zohra; Hula, Ibnu Rawandhy N; Hairuddin, Hairuddin; Adam, Muhammad Zikran (STIQ Amuntai, 2024)
This research aims to develop maharatul kalam teaching materials based on local wisdom. Based on the analysis of student needs, including the lack of availability of maharatul kalam teaching materials based on local wisdom, lack of interest of students in memorizing conversations, the ability of students who are still less proficient in speaking Arabic. The local wisdom used is limited in terms of tourist attractions in one area, traditional houses, traditional colors, food, and traditional clothing. This research method is D&D Design and Development. The subjects in this study were MTs Hubulo students with a total of 10 people and 15 students at MTs Khairul Hikmah Longalo. Data collection techniques and instruments in this study used observation, interviews, documentation and questionnaires. The data analysis technique of this study paired sample t test. The results of this study are based on the results of the implementation of pretest and post test values based on ttest > ttable values, which are 45,222>2,262. So it can be concluded that there is a very significant difference between the final value of the post test and pre test. And at the evaluation stage received a positive response from students so that this teaching material could be used in school. The contribution of this research is teaching materials in the form of printed books used by students in learning Arabic, especially the subjects of maharatul kalam (muhadatsah). The book also comes with audio.